Prevalence of family-based elder abuse and its associated factors in Gandaki Province of Western Nepal: A cross-sectional study. - Bharat Kafle; Aman Shrestha; Saruna Ghimire; Preeti Bhattarai; Pratik Bhattarai; Amod Kumar Poudyal (PLoS ONE)
Background Elder abuse is a rarely discussed public health and human rights issue in Nepal, largely due to traditional values emphasizing reverence for parents. These cultural norms can discourage recognition and reporting, especially within families. Consequently, nationwide or large-scale data on this issue is lacking. This study aims to estimate the prevalence and explore the factors associated with family-based elder abuse in Gandaki province, western Nepal. Methods A cross-sectional design was conducted interviewing 612 participants (≥ 60 years) in household settings. The study areas, representing mountain, hill and tarai regions of Gandaki province, were randomly selected using multistage stratified sampling process. The dependent variable was measured using 17-item elder abuse scale. Multivariable logistic regression explored the factors associated with elder abuse. Results More than half of the participants were from Nawalpur (57.2%), urban residents (68.1%), female (57.2%), without education (79.8%), and lived in multigenerational households (73.0%). The overall prevalence of elder abuse was reported at 56.4%, with caregiver neglect (50.8%) being the most prevalent sub-type. The prevalence was higher among females (66.6%) than males (42.8%). In adjusted multivariable logistic regression, those who were female (AOR = 2.56, 95%CI: 1.64-4.01), older than 70 years (AOR = 1.53, 95%CI: 1.03-2.29), reluctant to disclose health issues to family members (AOR = 2.13, 95%CI: 1.36-3.34), believed in traditional healers (AOR = 1.89, 95%CI: 1.28-2.77) and lived in nuclear households (AOR = 1.85, 95%CI: 1.19-2.89) had higher odds of elder abuse. Those living in rural areas (AOR = 0.39, 95%CI: 0.25-0.61), having formal education (AOR = 0.31, 95%CI: 0.10-0.95), and having good self-reported health (AOR = 0.23, 95%CI: 0.12-0.46) were associated with lower odds of elder abuse. Conclusions The study highlights a high prevalence of elder abuse, particularly caregiver neglect, with a disproportionate impact on women. Policy recommendations include raising awareness, strengthening legal protections, and improving caregiver training to meet these challenges effectively.